(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims at investigating the effect of gadget on the students’ interest in learning literature at higher education in Indonesia.This cross-sectional survey used an anonymous online questionnaire to obtain data from participants. Online questionnaire was distributed via WhatsApp. This is because during Covid-19 pandemic, the teaching – learning process taken place online. There were 92 participants in the study. The participants in this study were students from undergraduate degree, majoring Indonesian Language and Literature Study Program at the Faculty of Languages and Literature, State University of Makassar, Makassar, Indonesia. The online survey was done on February 2021. The instrument of the study was close-ended questionnaire consisting of demographic participants and some questions related to online learning practices in the outbreak of Covid-19 pandemic. Quantitative data were analyzed using descriptive statistics to present percentage, table, and graphic, and are therefore given comprehensive explanation and interpretation. Gadget has positive and significant effect on the students’ interest in learning literature at higher education.